Assessment of Joint and Fascia Manifestations in Chronic Graft‐Versus‐Host Disease1. Issue 4 (April 2014) - Inamoto, Yoshihiro; Pidala, Joseph; Chai, Xiaoyu; Kurland, Brenda F.; Weisdorf, Daniel; Flowers, Mary E. D.; Palmer, Jeanne; Arai, Sally; Jacobsohn, David; Cutler, Corey; Jagasia, Madan; Goldberg, Jenna D.; et al.
<x xml:space="preserve">Abstract</x> Objective To investigate the usefulness of various scales for evaluating joint and fascia manifestations in patients with chronic graft‐versus‐host disease (GVHD) after allogeneic hematopoietic cell transplantation, and to compare the scales in terms of simplicity of use and ability to yield reliable and clinically meaningful results. Methods In a prospective, multicenter, longitudinal, observational cohort of patients with chronic GVHD (n = 567), we evaluated 3 scales proposed for assessing joint status: the National Institutes of Health (NIH) joint/fascia scale, the Hopkins fascia scale, and the Photographic Range of Motion (P‐ROM) scale. Ten other scales were also tested for assessment of symptoms, quality of life, and physical functions. Results Joint and fascia manifestations were present at study enrollment in 164 (29%) of the patients. Limited range of motion was most frequent at the wrists or fingers. Among the 3 joint assessment scales, changes in the NIH scale correlated with both clinician‐ and patient‐perceived improvement of joint and fascia manifestations, with higher sensitivity than the Hopkins fascia scale. Changes in all 3 scales correlated with clinician‐ and patient‐perceived worsening, but the P‐ROM scale was the most sensitive in this regard. Onset of joint and fascia manifestations was not associated with subsequent mortality. Conclusion Joint and fascia manifestations are common in patients with chronic GVHD and should be assessed carefully in these patients. Our results support the use of the NIH joint/fascia scale and P‐ROM scale to assess joint and fascia manifestations. The NIH scale better captures improvement, while the P‐ROM scale better captures worsening. The utility of these scales could also be tested in the rheumatic diseases.